Health Promotion Using Jigsaw Cooperative Method for Enhancing Knowledge and Attitude on Anemia Prevention among Adolescents in Gunungkidul - Fa'ni, Renidya Asyura Muttabi Deya; Rosanti, Nadia Dian; Perwitasari , Dinar Rizqi (Jurnal Kesehatan Komunitas Indonesia, 2023)
Based on census data from Gunungkidul Health Department in 2022, 3 out of 10 female adolescents have anemia. Anemia is a health problem requiring more attention due to its influence on health and pregnancy complications among women in their reproductive age. Anemia among adolescents is related to their health knowledge and attitude. Health promotion using the cooperative jigsaw method is one of the effective methods to gain new knowledge among adolescents. This study aims to find the effectiveness of the cooperative jigsaw method on anemia prevention knowledge and attitude among female adolescents. This study uses quasi-experiment with pre-post test using control group. Using probability sampling, 60 female students from SMKN 1 Wonosari and SMKN 3 Wonosari are gathered to be this study’s respondents. The result shows that the average knowledge in the jigsaw cooperative group is 37,65 while in the conventional group is 23,35 with a P-value = 0,001. The average increase on attitude on the jigsaw cooperative group is 43,42 while in the conventional group is 17,58 with a P-value = 0,000. There is a significant difference in the average increase of knowledge and attitude in the cooperative jigsaw group on anemia prevention among female adolescents. Based on this, the cooperative jigsaw method is expected to be used as a method in health education.